Transmission tower environment monitoring using UAV - Redzuwan R.M.; Din N.M.; Baharuddin M.Z.; Mustafa I.S.; Omar R.C. (Institute of Physics Publishing, 2023)
Power utility engineers used to conduct ground survey to collect topographic data. Therefore, they can get detailed and accurate information, but these techniques take a lot of labors and expenses, and spending times for the surveying. An attractive solution to the ground survey is using images taken using Unmanned Aerial Vehicle (UAV). Images captured from UAV can be collected quickly and efficiently over the same area covered in the land survey, in a fraction of the time. The purpose of this research is to mosaic the large numbers of spectral images together into a region wide panoramic image which allows experts to analyze the data for transmission tower monitoring purposes. Published under licence by IOP Publishing Ltd.